MDS-110 SELECT-MDS-1 Trial in Progress: A Phase 3 Randomized, Double-Blind, Placebo-Controlled Study of Tamibarotene/Azacitidine Versus Placebo/Azacitidine in Newly Diagnosed Adult Patients Selected for RARA-Positive Higher-Risk MDS - DeZern, Amy; Fenaux, Pierre; Deeren, Dries; Campelo, Maria Diez; Lübbert, Michael; Krishnamurthy, Pramila; Nagy, Zsolt; Basak, Grzegorz; Ová, Anna Jonáš; Geissler, Klaus; Ofran, Yishai; Volkert, Angela; et al. (Clinical lymphoma, myeloma & leukemia, 2022)
CONTEXT: A novel genomically defined subset of higher-risk myelodysplastic syndrome (HR-MDS) patients with an actionable target characterized by overexpression of RARA has been identified (McKeown 2017). Approximately 30% of HR-MDS patients are RARA-positive by a blood-based biomarker test (Vigil 2017). Tamibarotene is an oral selective RARα agonist with potential for clinical benefit in RARA-positive HR-MDS patients, irrespective of mutation or cytogenetic risk. Initial clinical data in RARA-positive relapsed/refractory HR-MDS showed myeloid differentiation, improved blood counts, and reduced bone marrow blasts, including one patient who achieved marrow complete remission with hematologic improvement (Jurcic 2017). Tamibarotene/azacitidine led to a CR/CRi rate of 61% with rapid onset of response in RARA-positive newly diagnosed (ND) unfit AML patients, including those with low blast count (≤30%) AML, and a majority of patients achieved or maintained transfusion independence (de Botton 2020). Tamibarotene/azacitidine was generally well tolerated with no increase in myelosuppression compared with azacitidine alone (de Botton 2020). Historical precedent demonstrating similar clinical outcomes in HR-MDS and low blast count AML (Estey 2022) supports further development of tamibarotene/azacitidine in HR-MDS to improve clinical outcomes of standard of care treatment with hypomethylating agents (HMAs). OBJECTIVE: To characterize and compare the CR rate of tamibarotene/azacitidine to placebo/azacitidine in RARA-positive ND HR-MDS patients. Secondary objectives include comparisons of overall response rate, event-free survival, overall survival, transfusion independence, and safety. DESIGN: Global, Phase 3, randomized, double-blind, placebo-controlled trial (NCT04797780). Approximately 190 patients will be randomized 2:1, providing 90% power to detect the difference in CR rates between the experimental and control arms. PATIENTS: The included patients will be RARA-positive based on investigational assay and ND with HR-MDS by WHO classification (Arber 2016) with an IPSS-R risk category of very high, high, or intermediate and a blast count >5% at baseline. Patients with prior treatment for MDS with any HMA, chemotherapy, or transplant are excluded. INTERVENTION: Azacitidine will be administered at 75 mg/m2 IV/SC daily on days 1-7 (or 1-5, 8-9) followed by tamibarotene/placebo at 6 mg BID orally on days 8-28 of each 28-day cycle. MAIN OUTCOME MEASURES: Response is assessed per the modified IWG MDS criteria (Cheson 2006).
Keywords: benzoáty; výsledek terapie; Benzoates; Modafinil; Tetrahydronaphthalenes; myelodysplastické syndromy; modafinil; tetrahydronaftaleny; Treatment Outcome; Adult; akutní myeloidní leukemie; Azacitidine; lidé; dospělí; Leukemia, Myeloid, Acute; Humans; azacytidin; Myelodysplastic Syndromes